2015
DOI: 10.1136/thoraxjnl-2014-206488
|View full text |Cite
|
Sign up to set email alerts
|

A role for whey acidic protein four-disulfide-core 12 (WFDC12) in the regulation of the inflammatory response in the lung

Abstract: What is the key question?Does WFDC12 possess innate defence properties similar to other WFDC proteins in the lung such as SLPI and elafin? What is the bottom line?We have functionally characterised a member of the WFDC family of proteins, WFDC12, and have shown it to possess antiprotease and anti-inflammatory activity and to be present at elevated levels in the respiratory tract of patients with acute respiratory distress syndrome (ARDS). Why read on?Given its properties we speculate that WFDC12 may play a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…After 16 h of LPS treatment, TLR-4 showed a slight increase, indicating that it is essential for the activation of the immune response induced by LPS. It has been reported that activation of TLR4 by its principal agonist, LPS, results in an immunostimulatory intracellular signaling pathway leading to the activation of the transcriptional factor, NFκB [ 12 ]. Our data show that TLR4 expression was inhibited by shWfdc21, and then responded rapidly to LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 16 h of LPS treatment, TLR-4 showed a slight increase, indicating that it is essential for the activation of the immune response induced by LPS. It has been reported that activation of TLR4 by its principal agonist, LPS, results in an immunostimulatory intracellular signaling pathway leading to the activation of the transcriptional factor, NFκB [ 12 ]. Our data show that TLR4 expression was inhibited by shWfdc21, and then responded rapidly to LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Wfdc family members are critical in occurrence of inflammation. In the lungs, Wfdc12 regulates the inflammatory response [ 12 ]. Wfdc1 is a key modulator of inflammatory and wound repair responses.…”
Section: Introductionmentioning
confidence: 99%
“…SLPI is up-regulated in the epidermis of psoriasis patients and in injured skin and is induced during the proliferation of keratinocytes [ 31 ]. On the other hand, WFDC12 is a member of the whey acidic protein (WAP) family [ 32 ] and WFDC12 levels in bronchoalveolar lavage fluid are increased in inflammatory respiratory conditions [ 33 ]. The roles of SLPI and Wfdc12 in the skin are not fully understood, but the up-regulation of those proteins in TGM1 deficiency might contribute to innate defense responses of the skin through anti-protease, anti-microbial and/or anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval for the use of these samples was obtained from the Queen's University Belfast School of Medicine, Dentistry and Biomedical Science Research Ethics Committee (Belfast, UK). The lungs were perfused ex vivo based on previously described methods [32,33]. Experimentation ceased 4 h after LPS instillation, upon which tissue samples for histology were taken from LPS-perfused lobes [32].…”
Section: Human Lung Tissuementioning
confidence: 99%
“…The lungs were perfused ex vivo based on previously described methods [32,33]. Experimentation ceased 4 h after LPS instillation, upon which tissue samples for histology were taken from LPS-perfused lobes [32]. Lung tissue sections from CF patients were obtained from the University of Newcastle (Newcastle upon Tyne, UK).…”
Section: Human Lung Tissuementioning
confidence: 99%